In vitro formation of the blood–testis barrier during long-term organotypic culture of human prepubertal tissue: comparison with a large cohort of pre/peripubertal boys. (12th March 2018) - de Michele, F; Poels, J; Giudice, M G; De Smedt, F; Ambroise, J; Vermeulen, M; Gruson, D; Wyns, C
Abstract: STUDY QUESTION: How does the formation of the blood–testis barrier (BTB), as reflected by the expression of connexin 43 and claudin 11 proteins during the pubertal transition period, take place in vitro compared to samples from a large cohort of pre/peripubertal boys? SUMMARY ANSWER: The BTB connexin 43 and claudin 11 expression patterns appeared to be partially achieved in organotypic culture when compared to that in samples from 71 pre/peripubertal patients. WHAT IS KNOWN ALREADY: Although alterations in the protein expression patterns of the BTB, whose main components are connexin 43 and claudin 11, are known to be associated with impaired spermatogenesis in mice and adult men, there is a lack of knowledge on its formation in pre–peripubertal human tissue both in vitro and in vivo . Moreover, despite Sertoli cell (SC) maturation during long-term organotypic culture of immature testicular tissue (ITT), initiation of spermatogenesis has not yet been achieved. STUDY DESIGN, SIZE, DURATION: Histological sections from 71 pre–peripubertal patients were evaluated for the formation of the BTB acting as in vivo controls according to age, SC maturation, clinical signs of puberty and germ cell differentiation. Testicular tissue fragments retrieved from three prepubertal boys were cultured in a long-term organotypic system to analyze the BTB formation and expression pattern in correlation with SC maturation. PARTICIPANTS/MATERIALS, SETTING, METHODS: Testicular histological sections from 71 patients aged 0–16 years who underwent a biopsy between 2005 and 2014 to preserve their fertility before gonadotoxic treatment were examined. Immunohistochemistry (IHC) results for connexin 43 and claudin 11 as BTB markers, using a semi-quantitative score for their expression, and for Anti-Mullerian hormone (AMH), as SC maturation marker, were analyzed. Germ cell differentiation was evaluated on Hematoxylin–Eosin sections. Tanner stages at the time of biopsy were recorded from medical files. A longitudinal analysis of connexin 43, claudin 11 and AMH expressions on immunohistological sections of organotypic cultured testicular tissue from three prepubertal boys who underwent a biopsy for fertility preservation was performed. Immunostaining was evaluated at culture Days 0, 1, 3, 10, 16, 27, 32, 53, 64 and 139 for two different types of culture media. MAIN RESULTS AND THE ROLE OF CHANCE: Immunohistochemical control sections showed progressive maturation of SCs, as shown by the decrease in AMH expression, with increasing age ( P ≤ 0.01) and the AMH expression was negatively correlated with the expression of connexin 43 and claudin 11 ( P ≤ 0.01 for both proteins). Androgen receptor (AR) expression increased with age ( P ≤ 0.01) and was significantly correlated with the expression of connexin 43 ( P = 0.002) and claudin 11 ( P = 0.03). A statistical correlation was also found between the reduction of AMH expression and both the advancement of Tanner stages ( P ≤ 0.01) and the differentiation of germ cells ( P ≤ 0.01). Furthermore, positive correlations between BTB formation (using connexin 43 and claudin 11 expression) and age ( P ≤ 0.01 for both the proteins), higher Tanner stages ( P ≤ 0.001 and P ≤ 0.01 for connexin 43 and claudin 11, respectively), and presence of more advanced germ cells ( P ≤ 0.001 for both proteins) were observed. In the subanalysis on organotypic cultured ITT, where a significant decrease in AMH expression as a marker of SC maturation was already reported, we showed the onset of expression of connexin 43 at Day 16 ( P ≤ 0.001) and a constant expression of claudin 11 from Days 0 to 139, for all three patients, without differences between the two types of culture media. LARGE SCALE DATA: N/A. LIMITATIONS REASONS FOR CAUTION: Accessibility of prepubertal human testicular tissue is a major limiting factor to the analysis of cultured tissue samples from a wide number of patients, as would be needed to assess the in vitro development of the BTB according to the age. The impossibility of performing longitudinal studies on in vivo BTB formation in the same patient prevents a comparison of the time needed to achieve effective BTB formation and protein expression patterns in vivo and in vitro . WIDER IMPLICATIONS OF THE FINDINGS: To the best of our knowledge, this is the first report describing the expression of two BTB proteins in samples from a cohort of prepubertal and peripubertal boys, for the in vivo pattern, and in cultured ITT from a few prepubertal boys, for the in vitro evaluation. Since the formation of this barrier is essential for spermatogenesis and because little is known about its protein expression patterns and development in humans, a deeper understanding of the testicular microenvironment is essential to improve ITT in vitro culture conditions. The final aim is to restore fertility by acheiving in vitro differentiation of spermatogonial stem cells, using cryopreserved ITT collected before gonadotoxic therapies. STUDY FUNDING AND COMPETING INTEREST(S): Funding was received from Fonds National de la Recherche Scientifique de Belgique (Grant Télevie Nos. 7.4554.14F and 7.6511.16) and Fondation Salus Sanguinis. No conflict of interest has to be disclosed.